2019
DOI: 10.3389/fmed.2019.00082
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preference Studies During Early Drug Development: Aligning Stakeholders to Ensure Development Plans Meet Patient Needs

Abstract: Although patient preferences have been studied broadly for marketed products or around the time of submission to authorities and launch, patient preference studies have rarely been used during the early drug development phases. In this paper, we formulate three hypotheses supporting the use of patient preference studies in early product development: (1) integration of the patient perspective into the development process from phase 1 onwards will result in healthcare solutions with outcomes that best address pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 65 publications
0
51
0
1
Order By: Relevance
“…Guidance for the incorporation of patient preference measurements into drug development, regulatory, and reimbursement decision-making processes is evolving [3,32] and multi-stakeholder initiatives such as IMI PREFER (Innovative Medicines Initiative's The Patient Preferences in Benefit-Risk Assessments during the Drug Life Cycle project) are actively working to fill this gap [32]. There is a need for early engagement in dialogue with regulatory agencies and HTA bodies on scientific advice to discuss patient needs, preferences, and implications thereof for clinical trial design and evidence collection [8]. This step is crucial since, eventually, HTA agencies will be one of the recipients of any product submissions that will be developed through trials using the insights generated through such a PFDD exercise and would need to make reimbursement decisions after recognizing the value that such products offer to patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…Guidance for the incorporation of patient preference measurements into drug development, regulatory, and reimbursement decision-making processes is evolving [3,32] and multi-stakeholder initiatives such as IMI PREFER (Innovative Medicines Initiative's The Patient Preferences in Benefit-Risk Assessments during the Drug Life Cycle project) are actively working to fill this gap [32]. There is a need for early engagement in dialogue with regulatory agencies and HTA bodies on scientific advice to discuss patient needs, preferences, and implications thereof for clinical trial design and evidence collection [8]. This step is crucial since, eventually, HTA agencies will be one of the recipients of any product submissions that will be developed through trials using the insights generated through such a PFDD exercise and would need to make reimbursement decisions after recognizing the value that such products offer to patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…In DED as in other diseases patient preference research has the potential to revolutionise healthcare practice by allowing an individualised approach to treatment in accordance with the needs expressed by the patient 7. When conducted early in the product development lifecycle, patient preference studies can inform the design of clinical trials (eg, through the inclusion of patient-reported outcomes (PROs)), ensuring that outcomes that matter to patients are captured 8. With an increasing trend towards capturing relevant PROs in clinical trials, patient-centric information becomes an important input to value frameworks for evaluating new therapeutic interventions, to ensure they deliver value to the patient 8.…”
Section: Introductionmentioning
confidence: 99%
“…12 There have also been calls for improved alignment of stakeholders on patient needs early on in the drug development process. 13 Physicians are typically a major stakeholder that interacts directly with patients, which is why it is important for their preferences to be known and aligned with the other stakeholders. This paper takes a step further to align NASH stakeholders on their preferences and can be used in the future to guide research and develop awareness programmes for the benefit of patients.…”
Section: Discussionmentioning
confidence: 99%